Wood‐Derived Monolithic Carbon Materials and Their Functional Applications. Issue 6 (14th April 2022) - Sun, Yating; He, Zhaocai; Wei, Yuan; Liu, Gonggang; Liu, Rukuan; Hu, Jinbo; Liu, Huaifei; Zhang, Xiang; Yuan, Guangming
Abstract: Wood‐derived monolithic carbon materials have attracted increasing attention because of the unique porous structure, renewability, and easy processing. They are frequently used as a structural functional material in energy, environment, catalysis, and other applications recently. Wood‐derived monolithic carbon materials still exhibit the interconnected capillary array structure of wood which is in favor of mass transfer and energy storage/conversion offering application performance and prospect. Herein, wood‐derived monolithic carbon materials, from preparation to function application, are summarized. Various wood raw materials and carbonization methods are described in this work, as well as their impressive application performance in different fields. The aim is to provide an overview of the different monolithic carbon materials obtained from bulk wood which are employed for various functional applications, including energy storage/conversion, environmental conservation, solar steam generation devices, catalysis, and microwave absorption. This review will deepen the understanding of wood‐derived monolithic carbon utilization and inspire new ideas in the area of designing advanced wood‐based materials. Abstract : In addition to the advantages of renewability, abundance, low cost, and ease of processing, wood‐derived carbon with the superiority of natural its unique porous structure is a desirable monolithic functional material. Here, wood‐derived monolithic carbon materials, from preparation to function applications in energy, catalysis, environment treatment and other fields, and their potential future research directions are summarized.